Atmospheric ion spectra and the rate of voltage decay of an aspirated cylindrical capacitor - Aplin, K (2004)
Aspirated cylindrical capacitors are commonly used instruments for atmospheric ion measurements, more of which are needed for climate and pollution studies. However the classical theory of one operating mode of this instrument is based on an approximation, which may introduce errors in ion measurement. A modification to the classical theory of the instrument is consequently proposed. Applying this modification enables ion mobility spectrum information to be extracted from the rate of voltage decay of the aspirated capacitor in air. It can also be used to improve air conductivity measurements.